Pengujian Validitas Media Pembelajaran Berbasis Android Pada Mata Pelajaran Adminitrasi Server Jaringan (ASJ) - Yuliawati Yunus; Indra Wijaya; Ihsanul Kamil (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2020)
This research was motivated by the problem of limited learning resources at SMKN 3 Padang. This research and development aims to produce a product in the form of Android-Based Learning Media at SMK N 3 Padang and to test the validity for the feasibility of the learning media product. This research uses research and development ((R&D) methods. This research method uses analysis (ADDIE Model), with the design and development steps as follows: Analysis (analysis), Design (design), Develop(development), Implementation (implementation ) and Evaluation (evaluation). for testing the validity of this study is at the Develop stage by using three validators as experts for the feasibility of Android-based learning media on ASJ subjects. The results of validity testing by experts. Learning based on Android is 80.00%, so the level of validity can be interpreted to be very valid to use. Based on the assessment and expert input and the results of field trials of Android-based learning media, it has been tested for feasibility, excellence, and can be used in the learning process at SMK N 3 Padang .